Alkalising agents in urinary tract infections: theoretical contraindications, interactions and synergy - Oisín N. Kavanagh (SAGE Publishing, 2022)
Introduction: Alkalising agents have the potential to enhance the efficacy of many antimicrobial agents used in the treatment of Urinary Tract Infections; they also have the potential to cause significant patient harm if used incorrectly. This work seeks to illustrate and quantify these risks and synergies by modelling drug solubility and supersaturation against pharmacokinetic data for commonly used antibiotic agents. Methods: Solubility-pH relationships are employed to quantify the crystalluria risk for compounds which may be reasonably expected to be co-prescribed-or co-administered-with urinary alkalisers (amoxicillin, nitrofurantoin, trimethoprim, sulfamethoxazole and ciprofloxacin). These results are correlated against reports of crystalluria in the literature and in the EU Adverse Drug Reaction database. Results and Discussion: We find a correlation between the maximum theoretical supersaturation attainable and crystalluria reports for sulfamethoxazole, amoxicillin and ciprofloxacin. Shifts in urine pH which can be induced by alkalising agents may produce supersaturated states (and thus induce crystalluria) and may also affect antimicrobial efficacy. The importance of employing biorelevant media to improve predictive capacity of this analysis is also discussed. Conclusion: Despite their widespread use, alkalising agents have significant effects on the pharmacokinetics of the most common drugs used to treat UTIs. With self-care set to increase, all OTC products should be critically re-evaluated to ensure patient safety, particularly within contexts where healthcare professionals are not involved in treatment selection. This analysis suggests a need for consistency across patient and healthcare professional documents to improve clarity. Plain Language Summary OTC Alkalising agents need additional warning information Alkalising agents (e.g., sodium and potassium citrate) can be purchased in many locations without the supervision of a healthcare professional. Although they are thought as innocuous agents, alkalisers can greatly influence the way some antibiotics behave in the body and this can potentially cause patient harm. This work illustrates these risks and synergies by modelling drug solubility and supersaturation against pharmacokinetic data for commonly used antibiotic agents. Manufacturers and patients should be aware that the use of alkalising agents with these drugs (and potentially many others) may cause unintended consequences.